Compact laboratory-based X-ray microscope enabling nondestructive 3D structure acquisition of mouse nephron with high speed and better user accessibility. (2nd July 2022) - Kunishima, Naoki; Takeda, Yoshihiro; Hirose, Raita; Kume, Satoshi; Maeda, Mitsuyo; Oguchi, Akiko; Yanagita, Motoko; Shibuya, Hirotoshi; Tamura, Masaru; Kataoka, Yosky; Murakawa, Yasuhiro; Ito, Koichiro; et al.
Abstract: X-ray microscopes adopting computed tomography enable nondestructive 3D visualization of biological specimens at micron-level resolution without conventional 2D serial sectioning that is a destructive/laborious method and is routinely used for analyzing renal biopsy in clinical diagnosis of kidney diseases. Here we applied a compact commercial system of laboratory-based X-ray microscope to observe a resin-embedded osmium-stained 1-mm strip of a mouse kidney piece as a model of renal biopsy, toward a more efficient diagnosis of kidney diseases. A reconstructed computed tomography image from several hours of data collection using CCD detector allowed us to unambiguously segment a single nephron connected to a renal corpuscle, which was consistent with previous reports using serial sectioning. Histogram analysis on the segmented nephron confirmed that the proximal and distal tubules were distinguishable on the basis of their X-ray opacities. A 3D rendering model of the segmented nephron visualized a convoluted structure of renal tubules neighboring the renal corpuscle and a branched structure of efferent arterioles. Furthermore, another data collection using scientific complementary metal-oxide semiconductor detector with a much shorter data acquisition time of 15 min provided similar results from the same samples. These results suggest a potential application of the compact laboratory-based X-ray microscope to analyze mouse renal biopsy.